Artificial intelligence in the pharmaceutical industry of Ukraine: prospects for future development - Savchuk, A.; Borysiuk, I.; Mahanova, T. V.; Ihnatova, T.; Маганова, Тамара Валеріївна (My University, 2023)
Aims: To assess the Current State of AI Adoption, to Examine the Regulatory and Ethical Landscape of AI Implementation and to Identify Opportunities and Challenges in Ukraine. Methodology: A descriptive cross-sectional study Results: Currently, 4.1 billion people worldwide have sustainable Internet access, and 2.8 billion people make purchases online. This data highlights the significant global growth of Internet users and the increasing popularity of online shopping. The average digital user is now aged between 25 and 44. It indicates a shift in the age group of individuals actively using digital technologies. This demographic change has implications for businesses targeting digital consumers. Ukraine's pharmaceutical industry lags behind neighboring countries like the Czech Republic, Russia, and Poland in terms of AI utilisation, with only 10 publications related to AI in pharmaceuticals. This suggests a potential gap in research funding, industry investment, or academic expertise that needs to be addressed. Several prominent pharmaceutical companies in Ukraine are actively integrating AI and technology into their operations. These companies are focusing on various aspects, including drug discovery, diagnostics, innovation hubs, and investments in genetics and genomics. This highlights the industry's increasing adoption of AI. The challenges include the need for high-quality data, the difficulty in recruiting AI experts, regulatory compliance, and the financial constraints of funding AI initiatives. These challenges are critical considerations for pharmaceutical firms looking to leverage AI in their operations.